Development of molecular markers for Characterization of local pineapple (Ananascomosusvar. comosus) cultivars - Melvin John Kinsuat (2007)
Microsatellite markers have assumed a significant importance as molecular markers over the past few years. They are currently used extensively in population genetic studies, management and in conservation biology. This study aims to utilize microsatellite loci in order to investigate, assess and document the genetic diversity of the local pineapple varieties. Microsateillites were isolated from a single individual of the Sarawak variety obtained from Beaufort, Sabah. DNA was extracted from the plant and 5' anchored PCR was performed in order to isolate microsatellites using six degenerate primers LR1 [5'KKVRVRV (CT)â‚â‚€â»3â€™], UMS2 [5'-KKVRVRV (GT) )â‚â‚€â»3â€™], PCT1[5'-KKYHYHY (GA) )â‚â‚…â»3â€™], LR7 [5'-KKVRVRV (AG) )â‚â‚€â»3â€™], UMS1 [5'- KKYNSSH (ATG) )â‚ˆâ»3â€™]and PCT6 [5'-KKBNVSS (GATA)â‚†â»3â€™], to capture different repeat motifs. The resultant PCR products were then cloned into the pCR 2.1 TA TOPO vector and transformed into E. coli TOP10 competent cells. A total of 69 plasmid samples were sequenced of which 57 gave acceptable and clean DNA sequences. By using the 5' anchored PCR technique, a total of 123 distinct microsatellite loci were isolated, comprising of, 45 with dinucleotide repeats, 28 trinucleotide repeats, 48 with tetranucleotide repeats and two with hexanucleotide repeats. Twelve cryptic simple repeats were also identified. A total of 57 DNA sequences were deposited into GenBank and the accession numbers were obtained. A total of 35 microsatellite primers were designed based on the DNA sequences. Out the total, only 20 markers were found polymorphic and were used to characterize various pineapple varieties. These markers were used to screen 180 pineapples samples collected from Sabah and Sarawak representing the Sarawak, Madu and Mauritius varieties. Analysis data from the 20 loci revealed that the number of alleles per locus ranged from two to four and the average effective number of alleles, n of 2.1896. The Ho value ranged from 0.1705 to 1 with a mean of 0.7869. The FST value 0.1680 revealed high genetic variations among the populations and the gene flow, Nm was 1.2384. There was no evidence for significant linkage disequilibrium among the 20 loci examined. The Ewens-Watterson test for neutrality revealed that the majority of the loci were neutral and the pineapple populations investigated were deviates from HWE. The genetic distance value revealed that Kuching (Sarawak variety) and Miri (Sarawak variety) had the lowest genetic distance of 0.0263, while Beaufort (Sarawak) and KPD (Mauritius) had the highest of 0.4533. Next, the use of RAPD and SCAR markers were exploited to identify diagnostic markers that could be used to differentiate pineapple varieties. For this purpose, 80 pineapples representing the Sa rawak, Madu, Mauritius and Paun pineapple varieties were used. A total of five RAPD primers OPA3, OPA4, OPA8, OPA13 and OPA 15 were used to differentiate between these varieties. Primers OPA3, OPA4 and OPA13 generated polymorphic bands. Primer OPA3 generated distinct amplicons within the size range of 623 bp and 533 bp in the Mauritius variety and also 1018 bp in the Paun variety. Primer OPA4 generated an amplicon with the size of 480 bp in Mauritius variety and OPA13 generated an amplicon with the size of 700 bp in the Sarawak variety. The DNA fragments amplified by OPA3 for the Madu variety (768 bp, 623 bp and 523 bp) and the Paun variety (1018 bp) samples were excised purified and cloned using the TOPO TA Cloning kit (Invitrogen). Clones DSP1, DSP2, DSP9, DSP20, DKPD7 and DKP17 were sequenced. The DNA sequences were deposited into GenBank and the accession numbers were obtained. A total of six primers were designed DMAcSP1A, DMAcSP2A, DMAcSP9B, DMAc20B, DMAcKPD7 and DMAcKPD17. Out of the six, only DMAcSP2A amplified distinct loci at 606 bp in Paun variety and at 640 bp and 495 bp in Madu variety. A single RAPD polymorphism segregrating for varieties was used to derive a molecular single locus SCAR marker (DMAcSP2A, GenBank accersion number DQ875606) associated with the Paun variety. This SCAR marker can be applied for the identification of pineapple varieties and has potential for use in marker assisted selection. Microsatellite markers provide important data for the characterization of the local pineapple populations which are useful for germplasm management for the improvement of this important agronomic crop.